Landslide Susceptibility Modeling for Quarries Sites in Northeastern Missan: Using Fuzzy Logic Method - Zahraa R. Fakher ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Landslides are recognized as one of the most dangerous and often occurring natural catastrophes worldwide. Quarrying activities can dramatically enhance the danger of landslides by destabilizing slopes through drilling and heavy machinery movements. The digging process disrupts natural drainage patterns, resulting in water retention that damages soil and rock structures. The main justification of the present work is producing a landslide susceptibility model for quarries sites in northeastern Misan. This means an evaluated mixture of different indices. By applying the fuzzy logic method to remote sensing and GIS techniques. The study used spectral indices derived from multispectral Landsat. The thematic layers (indices) are: "Clay Minerals Ratio (CMR), Iron Oxide Ratio (IOR), Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), Normalized Difference Moisture Index (NDMI), Normalized Difference Water Index (NDWI), Bare Soil Index (BSI), and Normalized Difference Soil Index (NDSI)". The final landslide susceptibility map identified three risk zones: low, moderate, and high. The majority of quarries in northern areas are in a high-susceptibility zone, which indicates that quarry operations are a significant source of landslide danger, with northern quarries being high risk and northeastern quarries being moderate to low risk.DOI: https://doi.org/10.54633/2333-024-057-004